2016
DOI: 10.1007/s00784-016-1734-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of bone tissues surrounding dental implant systems with different treatments and healing periods

Abstract: Ability of energy absorption in the interfacial bone tissue can play a significant role in the long-term success of a dental implant system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…This fact might explain why bone is able to bear the impact of masticatory loading transmitted from the implant in absence of the periodontal ligament. 46 Baldassarri et al demonstrated that bone only reaches maturity after 5 years of loading and an increase of elastic modulus and hardness have been observed during that time in human retrieved implants. 47 Interestingly, a reduction in osteocyte density in samples after long period of loading have been reported, 48 and a possible explanation was the limited number of cells needed to maintain bone homeostasis after bone is matured, well aligned and biomechanically competent.…”
Section: Bone Remodeling Processmentioning
confidence: 99%
See 3 more Smart Citations
“…This fact might explain why bone is able to bear the impact of masticatory loading transmitted from the implant in absence of the periodontal ligament. 46 Baldassarri et al demonstrated that bone only reaches maturity after 5 years of loading and an increase of elastic modulus and hardness have been observed during that time in human retrieved implants. 47 Interestingly, a reduction in osteocyte density in samples after long period of loading have been reported, 48 and a possible explanation was the limited number of cells needed to maintain bone homeostasis after bone is matured, well aligned and biomechanically competent.…”
Section: Bone Remodeling Processmentioning
confidence: 99%
“…As aforementioned, peri‐implant implant bone undergoes remodeling after surgery trauma and due to the biological width establishment, but also it keeps in active bone remodeling during years as stimulated by the masticatory loading after the postimplantation healing . In a short‐term follow‐up study in dogs, Gyoon‐Kim et al .…”
Section: Biology Of the Bone Remodelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary stability is the progressive increase in stability as a consequence of the dynamic interrelationship between new bone formation and remodelling occurring at the bone-implant interfacial zone [17]. In the literature it is demonstrated that the implant success depends on the quality and quantity of the bone as most important factors [18][19][20]. Bone resorption and healing delay are the result of implant failure due to weak bone quantity and quality.…”
mentioning
confidence: 99%